Oxford Research Encyclopedia of Politics 2017
DOI: 10.1093/acrefore/9780190228637.013.586
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Peacekeeping Operations

Abstract: Peacekeeping has been one of the main conflict management tools used by the international community to restore or safeguard peace and security. Since 1948, the United Nations has established 70 peace operations and has substantially evolved, adopting approaches to peace that extend beyond purely military concerns. Indeed, the promises of peacekeeping as effective instrument of conflict reduction may, to some extent, explain the evolution toward multidimensional missions and the unprecedented number of peacekee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(37 citation statements)
references
References 57 publications
0
37
0
Order By: Relevance
“…Numerous large-n statistical studies have explored the relationship between third-party peacekeeping and different forms of violence (Dorussen 2014;Gizelis, Dorussen and Petrova 2016); Di Salvatore and Ruggeri 2017;Sandler 2017). What is most striking about these studies is the consistency of their findings.…”
Section: What the Current Evidence Revealsmentioning
confidence: 99%
“…Numerous large-n statistical studies have explored the relationship between third-party peacekeeping and different forms of violence (Dorussen 2014;Gizelis, Dorussen and Petrova 2016); Di Salvatore and Ruggeri 2017;Sandler 2017). What is most striking about these studies is the consistency of their findings.…”
Section: What the Current Evidence Revealsmentioning
confidence: 99%
“…There is near consensus that local conflict dynamics do not necessarily mirror national ones in civil war (Kalyvas, 2006), that national peace does not automatically trickle down (Autesserre, 2014;Cheng, Goodhand, & Meehan, 2018;Manning, 2003), and that local conflict resolution is crucial to building sustainable peace (Autesserre, 2017a). Research has further shown that peacekeeping contributes to a reduction in violence when large contingents deploy under robust mandates (Di Salvatore & Ruggeri, 2017), but its effect on local conflicts is less clear. Peacekeepers may contain the deadliness of local clashes but do not prevent local violence (Ruggeri, Dorussen, & Gizelis, 2017), while international efforts at local peacebuilding may yield ambiguous results (Autesserre, 2017a).…”
Section: Stabilization and Local Conflictsmentioning
confidence: 99%
“…Existing research agrees that peacekeeping works because it reduces the lethality, duration, and diffusion of civil wars (Beardsley and Gleditsch ; Di Salvatore and Ruggeri ; Fortna ; Gilligan and Sergenti ; Hultman, Kathman, and Shannon , ). This scholarship, however, focuses on violence perpetrated by armed political actors and largely neglects violence perpetrated by nonpolitically motivated actors—above all, criminal actors.…”
mentioning
confidence: 94%